Can wrist-worn devices and a smartphone application influence arm activity in children with unilateral cerebral palsy? A proof-of-concept study - Turner, Amie; Jackson, Dan; Officer, Eleanor; Boyne-Nelson, Chelsy; Zielinska, Zosia; Dinraj, Divya; Blickwedel, Jessica; Nappey, Tom; Rapley, Tim; Turpin, Heather; Cadwgan, Jill; Pearse, Janice Elizabeth; et al. (Frontiers in Rehabilitation Sciences, 2023)
Aim: To determine whether a wrist-worn triaxial accelerometer-based device and software (including smartphone application), incorporating feedback, is feasible, acceptable, and can lead to increased affected upper limb use during everyday activities in children with unilateral cerebral palsy (UCP). Methods: Study design: Mixed methods proof of concept study. Participants: Children aged 8-18 years with UCP; age-matched typically developing controls (“Buddies”), therapists. Intervention: Baseline (2 weeks): devices recorded arm activity. Active feedback (6 weeks): devices also gave vibratory prompts if affected arm activity fell below pre-set personalised thresholds (UCP group only; control group continued as per Baseline). Final 2 weeks: as baseline. Both groups accessed a smartphone application providing feedback on relative arm motion throughout the study. Assessment and analysis: ABILHAND-Kids questionnaires and MACS classifications captured baseline participant characteristics (UCP group). Accelerometer data was used to calculate relative arm activity (signal vector magnitude) corrected for time worn/day, and trends in relative arm activity examined using single case experimental design (both groups). In-depth interviews with families, “Buddies” and therapists assessed feasibility and acceptability of implementation. A framework approach was used for qualitative data analysis. Results: We recruited 19 participants with UCP; 19 buddies; and 7 therapists. Five participants (two with UCP) did not complete the study. Baseline mean (stdev) ABILHAND-Kids score of children with UCP who completed the study was 65.7 (16.2); modal MACS score was II. Qualitative analysis demonstrated acceptability and feasibility of the approach. Active therapist input for this group was minimal. Therapists appreciated the potential for summary patient data to inform management. Arm activity in children with UCP increased in the hour following a prompt (mean effect size z=0.261) for the non-dominant hand, and the dominant hand (z=0.247). However, a significant increase in affected arm activity between baseline and intervention periods was not demonstrated. Discussion: Children with UCP were prepared to wear the wristband devices for prolonged periods. Whilst arm activity increased bilaterally in the hour following a prompt, increases were not sustained. Delivery of the study during the COVID-19 pandemic may have negatively influenced findings. Technological challenges occurred but could be overcome. Future testing should incorporate structured therapy input.